2014
DOI: 10.1021/om5008488
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of CO2 to Trimethoxyboroxine with BH3 in THF

Abstract: Commercially available THF solutions of BH3·THF, which contain 0.5 mol % of NaBH4 as a stabilizing reagent for BH3·THF, react with 1 atm of CO2 at room temperature to form trimethoxyboroxine, (MeOBO)3, in 87% yield after 12 h. Since no reaction took place in the absence of NaBH4, NaBH4 was found to work as a promoter or catalyst for the reduction of CO2 with BH3 to the methoxy compound. A similar reaction using HCOONa in place of NaBH4 also gave (MeOBO)3 in comparable yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 63 publications
3
36
0
Order By: Relevance
“…Fontaine et al [79] and Mezailles et al [80] used the compound 82 and 83 featuring similar BH 2 fragment as catalyst of the reaction. The group of Mizuta used the simple hydroborate NaBH 4 84 to promote the hydride transfer to CO 2 in a similar fashion as metal hydride bond [81]. One or two equivalents of CO 2 reacts with the borate to form mono or bis-formatoborate complexes B(H) 4-x (O 2 CH) x that can then react with the hydroborane.…”
Section: Hydroborate Catalystsmentioning
confidence: 99%
“…Fontaine et al [79] and Mezailles et al [80] used the compound 82 and 83 featuring similar BH 2 fragment as catalyst of the reaction. The group of Mizuta used the simple hydroborate NaBH 4 84 to promote the hydride transfer to CO 2 in a similar fashion as metal hydride bond [81]. One or two equivalents of CO 2 reacts with the borate to form mono or bis-formatoborate complexes B(H) 4-x (O 2 CH) x that can then react with the hydroborane.…”
Section: Hydroborate Catalystsmentioning
confidence: 99%
“…[64]. However, there is only limited industrial viability in using hydrosilanes or hydroboranes for transforming CO2 into methanol and the most promising reductant for commercialization of a CO2 to methanol process is molecular hydrogen [65].…”
Section: Rationalizing the Catalytic Activity Of Ambiphilic Moleculesmentioning
confidence: 99%
“…To our surprise, repeating the experiment with the same parameters while omitting the catalyst showed that 21% of the silane was consumed after 4 h and as much as 82% was consumed after 24 h (entries [14][15]. With a catalytic loading of 0.01 mol%, complete conversion of the silanes was achieved after 48 hours.…”
mentioning
confidence: 93%